New insights into the genesis of the "Poznań clays" - upper neogene of Poland - Maciaszek, Piotr; Chomiak, Lilianna; Urbański, Paweł; Widera, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present study focuses on the upper Neogene deposits, called the "Poznań Clays", that cover more than 75,000 km2 of Poland. They are situated between the first midPolish lignite seam and the glaciogenic deposits of the Pleistocene age. Lithostratigraphically, the "Poznań Clays" belong to the uppermost portion of the lignite-bearing Grey Clays Member and the whole Wielkopolska Member (Poznań Formation).
Keywords: overbank deposits; palaeosols; palaeochannels; anastomosing river; Neogene of central Poland